Methodical Techniques for Analyzing the Poetic Context of the Book N. Chernova “Steppe Babylon” in High Education (Journal of Educational Sciences, 2019)
The article discusses the methodological techniques for the analysis of poetic elements in the book of prose of the Kazakh poetess N. Chernova “Steppe Babylon”. In the process of teaching analysis, philology students form an idea of the originality of the genre structure of the book, its poetic signs are revealed. Analysis of the book of prose by Nadezhda Chernova, taking into account the unity of the epic and poetic context, improves the students’ analytical skills, helps them to understand the peculiarities of the author’s “Steppe Babylon” style, to get an accurate idea of the genre structure of the work. Analysis of the artistic world of the work of Nadezhda Chernova will allow students to feel the author’s moods and feelings, to realize the richness of the spiritual life reflected in her prose with the help of various artistic techniques and means, including those used by her in poetry. Through the use of correctly chosen methodological heuristic techniques, it is possible to achieve an adequate perception and understanding by students of the genre content of the book Steppe Babylon, which is necessary for a deeper understanding of this work. Studying the poetics and semantic space of the book of prose by Nadezhda Chernova on the basis of heuristic analysis contributes to the further literary development of students, improving their analytical skills.Key words: heuristic situation, heuristic conversation, methodical techniques, activation of thinking, motive, plot, genre structure, poetic beginning, poetic context, Nadezhda Chernova, “Steppe Babylon”.